Suicide among post-Arabellion refugees in Germany - Nensy Thu Ha Le; Jon Genuneit; Gerald Brennecke; Georg von Polier; Lars White; Daniel Radeloff (BJPsych Open)
Background Although immigrants are considered to be vulnerable to mental illness, there is limited knowledge regarding their suicide mortality.